CLINICAL AND RADIOGRAPHIC EVALUATION OF DIRECT PULP CAPPING PROCEDURES PERFORMED BY POSTGRADUATE STUDENTS - Monea, Monica; Sitaru, Alexandru; Hantoiu, Tudor (European Scientific Journal, ESJ, 2015)
Aim of study. To evaluate the outcome of direct pulp capping procedures in permanent teeth performed by postgraduate students during their training program in Endodontics. Material and Methods. 39 patients with dental pulp exposures were evaluated clinically and radiologically after direct pulp capping procedure and followed for at least 24 months. The results were considered successful if the tooth remained vital, with neither symptoms nor periapical radiolucency. Results. The success rate of direct pulp capping was 59.3%, associated more with traumatic exposure than with carious exposure (75% versus 29.03%, p˂0,001) and more with class I occlusal restorations (85.71%) than with proximal restorations (class II 59.09%, class III 66.67%, p=0,009). Conclusions. The choice of direct pulp capping procedures in caries lesions or traumatic exposure must be supported by a correct diagnosis, evaluation of pain history, symptoms and radiographic examination. The best results are noted in young patients with recent traumatic exposures.